COMBINING GREEN BUILDING AND LEAN CONSTRUCTION TO ACHIEVE MORE SUSTAINABLE DEVELOPMENT IN SOUTH AFRICA - Watkins, J; Sunjka, Bernadette (The South African Journal of Industrial Engineering, 2020)
This paper explores the synergies that exist between lean construction and green building across all the development phases in a construction project to enhance sustainable development practices in South Africa. Using a systematic literature review, 68 articles were selected and coded. The findings indicate that: (i) lean construction and green building practices, principles, techniques, tools, and technologies can be simultaneously implemented across all phases of development, and offer multidimensional benefits in each; (ii) building information modelling plays a crucial role in assisting and facilitating lean construction and green building, mutually reinforcing each other throughout a development; (iii) prefabricated construction is becoming a popular way in which lean construction and green building are interacting and supporting each other; and (iv) the interaction between lean construction and green building can help to achieve more sustainable development in South Africa.